2023
DOI: 10.1186/s41256-023-00297-z
|View full text |Cite
|
Sign up to set email alerts
|

Screen time among school-aged children of aged 6–14: a systematic review

Abstract: Background Screen time refers to the time an individual spends using electronic or digital media devices such as televisions, smart phones, tablets or computers. The purpose of this study was to conduct systematic review to analyze the relevant studies on the length and use of screen time of school-aged children, in order to provide scientific basis for designing screen time interventions and perfecting the screen use guidelines for school-aged children. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…They correctly identified "healthy" and "unhealthy" foods. It is also worth noting that sedentary behaviors (such as watching TV, using computers, and reading books or magazines) and low physical activity influence the increased consumption of these products [51][52][53][54]. In this study, the profile of students with low physical activity was described as "indifferent" in terms of dietary behavior, and their diet was characterized by numerous nutritional mistakes.…”
Section: Discussionmentioning
confidence: 81%
“…They correctly identified "healthy" and "unhealthy" foods. It is also worth noting that sedentary behaviors (such as watching TV, using computers, and reading books or magazines) and low physical activity influence the increased consumption of these products [51][52][53][54]. In this study, the profile of students with low physical activity was described as "indifferent" in terms of dietary behavior, and their diet was characterized by numerous nutritional mistakes.…”
Section: Discussionmentioning
confidence: 81%
“…Overexposure to electronic screen devices has become a common behavior among children and teens around the world and has been accentuated since the COVID-19 pandemic. The main screen-based devices most used by children and adolescents from six to 14 years of age include TV, computers, and cell phones/tablets [ 38 ]. In our study, TV and cell phones were the most reported devices.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence to show the positive associations between different aspects related to the movement [sufficient physical activity ( 4 ), limited screen time ( 5 ), and appropriate sleep duration ( 6 )] with the children and adolescent health.…”
Section: Introductionmentioning
confidence: 99%